Simplicity as an Artistic Strategy: An Analysis of Sapardi Djoko Damono's Poem “Aku Ingin” in the Perspective of Russian Formalism - Khofifah Indah Baitul Jannah; Atika Rosiana Widarwati; Yusro Edy Nugroho (Syntax Corporation Indonesia, 2026)
This research aims to prove that the simplicity in the poem